Deaths Among Children, Adolescents, and Young Adults with Down Syndrome. Issue 3 (12th April 2013) - Miodrag,, Nancy; Silverberg,, Sophie E.; Urbano, Richard C.; Hodapp, Robert M.
<x xml:space="preserve">Abstract</x> Background Although life expectancies in Down syndrome (DS) have doubled over the past 3–4 decades, there continue to be many early deaths. Yet, most research focuses on infant mortality or later adult deaths. Materials and Methods In this US study, hospital discharge and death records from the state of Tennessee were linked to examine 2046 hospitalized individuals with DS (85 died) in three age groups: children (1–9), adolescents (10–19) and young adults (20–29). Results Most deaths occurred to young adults, while children had the most hospitalizations. Leading causes of death were cardiovascular and pulmonary conditions, and patients who died had longer hospital stays. Proportions of female deaths rose in young adulthood, and disproportionately more African Americans died at each age period. Conclusion Mortality is high among young adults with DS. Special vigilance is needed for individuals with DS who are female, African American and in their 20s.